National and Sub-National Social Distancing Responses to Covid-19 - Terrence Iverson; Edward B. Barbier (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the effectiveness of sub-national actions to control a novel disease, such as Covid-19, in the absence of a national policy. Evidence is emerging that countries where sub-national governments have undertaken unilateral social distancing measures to combat the pandemic with little or no coordination have performed less well in controlling the spread of the disease. We explore analytically whether agreement on a common social distancing policy among sub-national governments, i.e. states or provinces, can lead to a better outcome than if each state or province pursues its own social distancing policy in isolation. A key feature of our model is that it accounts for the inter-jurisdictional spillover effects of each sub-national jurisdiction's policy choice with respect to social distancing. Our results show that, in the absence of a national mandatory agreement, a sub-national agreement with sufficient coordination of social distancing policy among states yields a more effective and efficient control of a pandemic compared to states choosing policy unilaterally. These findings strongly support calls for greater cooperation among and assistance for sub-national governments to improve the effectiveness of their social distancing efforts in controlling the pandemic.
Keywords: H41; H73; I18; 330; Covid-19; national policy; social distancing; sub-national jurisdiction